Preparação pedagógica para o ensino de bioquímica: a percepção de discentes da Pós-Graduação - (:unkn) unknown (Universidade Federal do Pampa, 2014)
In Brazil, teacher training for higher education occurs specifically in graduate programs (PPG) stricto sensu. However, those leaving are trained to research excellence, but with weaknesses in the context of teaching. As Biochemistry is interdisciplinary and has constituted practically his knowledge from the development of scientific research the PPG area follow the same strand. In this sense, this work investigates the spaces dedicated to teaching / education in the structure of the PPG in biochemistry from Brazil and designing students about the importance of pedagogical preparation for teaching careers. To this end, we conducted a survey of Brazil's distributed by PPG spaces and analyze the design students. We found that there are several spaces for teaching / education in PPG, although these have more character extension that formative. As the conceptions of students realize there is a real concern about the importance of pedagogical preparation for teaching biochemistry and his subsequent teaching practice. Thus we can see the extreme importance of consolidation and expansion of these spaces in PPG.
Pedagogical preparation for teaching biochemistry: the perception of students in the Graduate
Keywords: Ensino; Bioquímica; Ensino Superior; Formação de professores; Biochemistry; Higher education; Teacher training; CNPQ::CIENCIAS HUMANAS